Sosialisasi Pendaftaran Kartu Indonesia Pintar Kuliah (KIP-K) Bagi Siswa-Siswi Tidak Mampu di Malifut, Maluku Utara - Aji Saputra; Hijrasil Hijrasil; Saprudin Saprudin; Fatma Hamid; Nurdin Abdul Rahman; Halleyna Widyasari; Zandy Pratama Zain; Sartika Putri Sailuddin; Usman Sambiri; Nur Fajrhi; Iqbal Limatahu; Chumidach Roini; Ismi Musdalifah Darsan; Mardia Hi Rahman; Fitriningsih P. Mahmud; Abi Suar (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2025)
The Kartu Indonesia Pintar Kuliah (KIP-K) is a scholarship program provided by the government for high school graduates who excel academically but are economically disadvantaged and unable to continue their studies at university. The KIP-K program aims to increase opportunities for students to pursue higher education by providing monthly living expenses and tuition fees for students who meet the eligibility criteria. Through KIP-K, it is expected to create a competitive and well-educated generation of future leaders. In North Maluku Province, particularly in Malifut, North Halmahera Regency, many students still lack information about the KIP-K scholarship. Therefore, this community service activity aimed to provide insights into the importance of pursuing education at the university level and how underprivileged students can apply for the KIP-K scholarship. This activity was carried out at SMAN 4 Halmahera Utara and SMKN 2 Halmahera Utara. As a result of this socialization, students successfully created their own accounts and registered for the KIP-K scholarship. It is hoped that through this program, students will take advantage of higher education opportunities through KIP-K and be able to continue their studies and achieve their goals.